2017
DOI: 10.4244/eij-d-16-01014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of successful percutaneous coronary intervention of chronic total occlusions on myocardial perfusion and left ventricular function

Abstract: The vast majority of CTO patients with documented ischaemia and viability showed significant improvement in stress MBF and a reduction of ischaemic burden after successful percutaneous revascularisation with only minimal effect on LVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 21 publications
2
33
0
3
Order By: Relevance
“…Thirty‐four observational studies [including two abstracts ] with a total of 2804 patients met our inclusion criteria . Cardiac magnetic resonance imaging (CMR) was used to assess LVEF in nine studies while echocardiography was used in 10 studies . Other studies used left ventriculography or nuclear imaging, or did not specify the method used for assessing LVEF .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐four observational studies [including two abstracts ] with a total of 2804 patients met our inclusion criteria . Cardiac magnetic resonance imaging (CMR) was used to assess LVEF in nine studies while echocardiography was used in 10 studies . Other studies used left ventriculography or nuclear imaging, or did not specify the method used for assessing LVEF .…”
Section: Resultsmentioning
confidence: 99%
“…Only one randomized-controlled trial (RCT) was identified. 7 Thirty-four observational studies [including two abstracts 13,14 ] with a total of 2804 patients met our inclusion criteria. Cardiac magnetic resonance imaging (CMR) was used to assess LVEF in nine studies [14][15][16][17]29,32,33,40,41 while echocardiography was used in 10 studies.…”
Section: Characteristics Of the Included Studies And Quality Assessmentioning
confidence: 99%
“…However, the combined effect of a higher prevalence of CAD risk factors, prior (unrecognized) MI, and prior revascularization in patients with a CTO could hypothetically have led to relatively more microvascular disease in the CTO area, (partially) causing diminished hyperemic MBF and (non‐significantly) lower CFR in these patients . Using [ 15 O]H 2 O PET perfusion, it has previously been shown that MBF during hyperemia is inversely related to the extent of surrounding scar tissue in patients with a CTO …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, next to symptom recognition and viability detection, ischemia detection forms one of the pillars in judicious patient selection for CTO PCI. Major reductions in ischemia can be achieved after CTO PCI, however, it is more conservatively employed compared with PCI of a non‐CTO lesion . [ 15 O]H 2 O positron emission tomography (PET) is the gold standard for non‐invasive myocardial perfusion imaging, reflecting the composite of the epicardial as well as the microvascular bed, and enabling absolute quantification of myocardial perfusion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation